Mesenchymal Stem Cell Secretome: A Potential Tool for the Prevention of Muscle Degenerative Changes Associated With Chronic Rotator Cuff Tears. (January 2017) - Sevivas, Nuno; Teixeira, Fábio Gabriel; Portugal, Raquel; Araújo, Luís; Carriço, Luís Filipe; Ferreira, Nuno; Vieira da Silva, Manuel; Espregueira-Mendes, João; Anjo, Sandra; Manadas, Bruno; Sousa, Nuno; Salgado, António J.
Background: Massive rotator cuff tears (MRCTs) are usually chronic lesions with pronounced degenerative changes, where advanced fatty degeneration and atrophy can make the tear irreparable. Human mesenchymal stem cells (hMSCs) secrete a range of growth factors and vesicular systems, known as secretome, that mediates regenerative processes in tissues undergoing degeneration. Purpose: To study the effect of hMSC secretome on muscular degenerative changes and shoulder function on a rat MRCT model. Study Design: Controlled laboratory study. Methods: A bilateral 2-tendon (supraspinatus and infraspinatus) section was performed to create an MRCT in a rat model. Forty-four Wistar-Han rats were randomly assigned to 6 groups: control group (sham surgery), lesion control group (MRCT), and 4 treated-lesion groups according to the site and periodicity of hMSC secretome injection: single local injection, multiple local injections, single systemic injection, and multiple systemic injections. Forelimb function was analyzed with the staircase test. Atrophy and fatty degeneration of the muscle were evaluated at 8 and 16 weeks after injury. A proteomic analysis was conducted to identify the molecules present in the hMSC secretome that can be associated with muscular degeneration prevention. Results: When untreated for 8 weeks, the MRCT rats exhibited a significantly higher fat content (0.73% ± 0.19%) compared with rats treated with a single local injection (0.21% ± 0.04%; P < .01) or multiple systemic injections (0.25% ± 0.10%; P < .05) of hMSC secretome. At 16 weeks after injury, a protective effect of the secretome in the multiple systemic injections (0.62% ± 0.14%; P < .001), single local injection (0.76% ± 0.17%; P < .001), and multiple local injections (1.35% ± 0.21%; P < .05) was observed when compared with the untreated MRCT group (2.51% ± 0.42%). Regarding muscle atrophy, 8 weeks after injury, only the single local injection group (0.0993% ± 0.0036%) presented a significantly higher muscle mass than that of the untreated MRCT group (0.0794% ± 0.0047%; P < .05). Finally, the proteomic analysis revealed the presence of important proteins with muscle regeneration, namely, pigment epithelium-derived factor and follistatin. Conclusion: The study data suggest that hMSC secretome effectively decreases the fatty degeneration and atrophy of the rotator cuff muscles. Clinical Relevance: We describe a new approach for decreasing the characteristic muscle degeneration associated with chronic rotator cuff tears. This strategy is particularly important for patients whose tendon healing after later surgical repair could be compromised by the progressing degenerative changes. In addition, both precise intramuscular local injection and multiple systemic secretome injections have been shown to be promising delivery forms for preventing muscle degeneration.